Safety and effects of anti-obesity medications on weight loss, cardiometabolic, and psychological outcomes in people living with overweight or obesity: a systematic review and meta-analysisResearch in context - Leiling Liu; Zhiqi Li; Wenrui Ye; Pu Peng; Yurong Wang; Luqing Wan; Jiangnan Li; Mei Zhang; Yihua Wang; Runqi Liu; Danyan Xu; Jingjing Zhang (EClinicalMedicine)
Summary: Background: Overweight and obesity pose serious health challenges for individuals and societies. This study aims to facilitate personalised treatment of obesity by summarising recent research on weight-loss pharmacotherapies, with a focus on their effects on weight reduction, cardiometabolic health, psychological outcomes, and adverse events. Methods: This systematic review and meta-analysis included searches of Web of Science, PubMed, and Cochrane Central Register of Controlled Trials from inception to June 8, 2024. Randomised controlled trials evaluating weight-loss pharmacotherapies approved by the Food and Drug Administration (FDA) or European Medicines Agency (EMA) for treating overweight or obesity were included. Primary outcomes included changes in body weight, cardiometabolic indicators, psychological outcomes, and adverse events. Summary data was extracted from published reports. Random-effects meta-analyses were used to calculate weighted mean differences (WMDs), risk ratios (RRs), and 95% confidence intervals (CI). The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) system was used to assess the certainty of evidence for each pooled analysis. PROSPERO registration: CRD42024547905. Findings: A total of 154 randomised controlled trials (n = 112,515 participants) were included. Tirzepatide had the greatest weight-loss effect (WMD −11.69, 95% CI −19.22 to −4.15; P = 0.0024; I2 = 100.0%; moderate certainty), followed by semaglutide (−8.48, −12.68 to −4.27; P < 0.0001; I2 = 100.0%; moderate certainty). Tirzepatide had the strongest antihypertensive effect on both systolic (WMD −5.74, −9.00 to −2.48; P = 0.0006; I2 = 99.8%; moderate certainty) and diastolic blood pressure (WMD −2.91, −4.97 to −0.85; P = 0.0056; I2 = 99.8%; moderate certainty) and best reduced triglycerides (WMD −0.77, −0.85 to −0.69; P < 0.0001; I2 = 3.2%; high certainty), fasting glucose (WMD −3.06, −5.53 to −0.59; P = 0.015; I2 = 100.0%; moderate certainty), insulin (WMD −4.91, −8.15 to −1.68; P = 0.0029; I2 = 97.0%; moderate certainty), and glycated haemoglobin levels (WMD −1.27, −1.82 to −0.73; P < 0.0001; I2 = 100.0%; moderate certainty). Semaglutide (RR 0.83, 0.74–0.92; P < 0.0001; I2 = 0.0%; high certainty) and liraglutide (0.87, 0.79–0.96; P = 0.0059; I2 = 0.0%; high certainty) reduced the risk of major adverse cardiovascular events (MACEs). However, all three medications were associated with adverse gastrointestinal effects. Naltrexone/bupropion increased the risk of elevated blood pressure (RR 1.72, 1.04–2.85; P = 0.036; I2 = 0.0%; high certainty). Topiramate increased depression risk (RR 1.62, 1.14 to 2.30; P = 0.0077; I2 = 0.0%; high certainty), and phentermine/topiramate raised concerns about anxiety (RR 1.91, 1.09 to 3.35; P = 0.025; I2 = 29.5%; high certainty), sleep disorders (RR 1.55, 1.24–1.93; P < 0.0001; I2 = 0.0%; high certainty), and irritability (RR 3.31, 1.69–6.47; P < 0.0001; I2 = 0.0%; high certainty). No medication increased the risk of serious adverse events. Interpretation: For weight reduction, tirzepatide is the top choice, followed by semaglutide. Considering cardiometabolic risk factors, tirzepatide shows the best blood pressure- and glucose-lowering benefits, while semaglutide and liraglutide reduce the risk of MACEs. Naltrexone/bupropion carries a risk of increased blood pressure. Phentermine/topiramate should be used with caution due to its higher risk of psychological side effects. Despite limitations related to study heterogeneity, these findings provide valuable insights for weight management strategies across diverse individuals. Funding: National Natural Science Foundation of China, Leading Talents Program of Hunan Province, and Fundamental Research Funds for the Central Universities of Central South University.